2014
DOI: 10.1002/jez.1868
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and short‐term physiological consequences of PHA immune response in lesser kestrel nestlings

Abstract: Individual immune responses are likely affected by genetic, physiological, and environmental determinants. We studied the determinants and short-term consequences of Phytohaemagglutinin (PHA) induced immune response, a commonly used immune challenge eliciting both innate and acquired immunity, on lesser kestrel (Falco naumanni) nestlings in semi-captivity conditions and with a homogeneous diet composition. We conducted a repeated measures analyses of a set of blood parameters (carotenoids, triglycerides, β-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…For example, RMR following PHA administration did not increase in white-footed mouse ( Peromyscus leucopus , 3.24 mg kg -1 ) [17], Mongolian gerbils ( Meriones unguiculatus , 2.04‒3.20 mg kg -1 ) [19] or tuco-tucos ( Ctenomys talarum , ~1 mg kg -1 ) [20]. Our findings are also similar to those found in some birds, including the lesser kestrel ( Falco naumanni , 1.83 mg kg -1 ) [21], house sparrow ( Passer domesticus , 3.70 mg kg -1 ) [18], and Japanese quail ( Coturnix coturnix , 0.49‒0.59 mg kg -1 ) [47] suggesting that the inflammatory response is not an energetically costly process. In fact, only two studies have proven that inflammation might elicit a significant metabolic cost: RMR increased to a large extent (~30%) in house sparrow (3.70 mg kg -1 ) [15] and to a moderate extent (~5%) in the great tit ( Parus major , 5.71 mg kg -1 ) [18].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For example, RMR following PHA administration did not increase in white-footed mouse ( Peromyscus leucopus , 3.24 mg kg -1 ) [17], Mongolian gerbils ( Meriones unguiculatus , 2.04‒3.20 mg kg -1 ) [19] or tuco-tucos ( Ctenomys talarum , ~1 mg kg -1 ) [20]. Our findings are also similar to those found in some birds, including the lesser kestrel ( Falco naumanni , 1.83 mg kg -1 ) [21], house sparrow ( Passer domesticus , 3.70 mg kg -1 ) [18], and Japanese quail ( Coturnix coturnix , 0.49‒0.59 mg kg -1 ) [47] suggesting that the inflammatory response is not an energetically costly process. In fact, only two studies have proven that inflammation might elicit a significant metabolic cost: RMR increased to a large extent (~30%) in house sparrow (3.70 mg kg -1 ) [15] and to a moderate extent (~5%) in the great tit ( Parus major , 5.71 mg kg -1 ) [18].…”
Section: Discussionsupporting
confidence: 82%
“…Experimental work in homeothermic vertebrates indicates that the effects of PHA and LPS application on metabolic rate are not uniform. For example, PHA administration has been shown to induce large (30%) [15] or small increases in resting metabolic rate (RMR) in some organisms (~5%) [16], no increases in RMR [1721], and even decreases in RMR in others (-20‒-25%) [18]. Similarly, the effect of LPS administration on vertebrate RMR varies from large (~33‒40%) [22, 23] to small (~10%) [2426] or null [27, 28].…”
Section: Introductionmentioning
confidence: 99%
“… Details regarding MHC diversity: in Charbonnel et al () measured as heterozygosity at two different MHC loci (0/1, Dqa1 and Drb loci), and number of amino acid differences between alleles for both loci; in Cutrera et al (), Cutrera et al () measured as MHC heterozygosity (0/1); in Rodríguez et al () measured as the number of amino acid differences between MHC alleles; in Montano‐Frías et al () measured as the number of MHC loci present; in Lukasch et al () measured as the number of different functional MHC alleles (i.e., “supertypes,” based only on sites located within the PBR and characterized by physicochemical descriptors). Details regarding specific MHC alleles: in Cutrera et al (), Cutrera et al () presence/absence of MHC allele groups (groups defined according to their amino acid similarity); in Ekblom et al () presence/absence of specific allelic lineages (lineages defined according to their nucleotide similarity); in Rodríguez et al () presence/absence of MHC allele groups (two groups were defined based on the most frequent vs. infrequent alleles); in Montano‐Frías et al () presence/absence of specific MHC loci; in Sin et al () presence/absence of specific MHC alleles and haplotypes; in Lukasch et al () presence/absence of the most frequent functional MHC alleles (i.e., “supertypes,” based only on sites located within the PBR and characterized by physicochemical descriptors). …”
Section: Methodsmentioning
confidence: 99%
“…Less information is available from wild species' populations, with contrasting outcomes in the few studies available. Thus, whereas some studies have found support for associations of MHC variation and immunocompetence (Bonneaud, Richard, Faivre, Westerdahl, & Sorci, ; Charbonnel et al, ; Cutrera, Zenuto, & Lacey, ; Kurtz et al, ; Lukasch et al, ), others have provided no clear evidence for their existence (Bonneaud, Sinsheimer, Richard, Chastel, & Sorci, ; Cutrera, Zenuto, & Lacey, ; Ekblom, Hasselquist, & Sæther, ; Montano‐Frías, Vera‐Massieu, Álvarez‐Martínez, Flores‐Morán, & Acevedo‐Whitehouse, ; Rodríguez, Broggi, Alcaide, Negro, & Figuerola, ; Sin et al, ). Such contrasting results may indicate the absence of a general biological association between MHC variation and immunocompetence, which may arise only in certain species, populations and/or ecological contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Grey partridge ornamental colouration in males may, therefore, serve as a reliable signal of condition and health to females. Immune function has repeatedly been shown to be condition-dependent (Hõrak et al 2000;Rodríguez et al 2014). This is because mounting an immune response may be costly in terms of energy as well as resources (Martin et al 2003;Sears et al 2011;Moreno-Rueda 2010).…”
Section: Discussionmentioning
confidence: 98%